2021
DOI: 10.3389/feart.2021.749611
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Recently Released High-Degree Global Geopotential Models Based on Heterogeneous Geodetic and Ocean Data

Abstract: The development of the global geopotential model (GGM) broadens its applications in ocean science, which emphasizes the importance for model assessment. We assess the recently released high-degree GGMs over the South China Sea through heterogeneous geodetic observations and synthetic/ocean reanalysis data. The comparisons with a high resolution (∼3 km) airborne gravimetric survey over the Paracel Islands show that XGM2019e_2159 has relatively high quality, where the standard deviation (SD) of the misfits again… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Zingerle et al [16] noted that XGM2019e_2159 performs exceptionally well over oceans, showing comparable or even superior performance compared to earlier models. Furthermore, Wu et al [27] highlighted that alternative Global Geopotential Models (GGMs) exhibit reduced accuracy compared to XGM2019e_2159, with coastal zones being significantly affected. Table 1 presents data regarding the content of satellite data and the highest degree of order for the four models.…”
Section: Global Geopotential Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Zingerle et al [16] noted that XGM2019e_2159 performs exceptionally well over oceans, showing comparable or even superior performance compared to earlier models. Furthermore, Wu et al [27] highlighted that alternative Global Geopotential Models (GGMs) exhibit reduced accuracy compared to XGM2019e_2159, with coastal zones being significantly affected. Table 1 presents data regarding the content of satellite data and the highest degree of order for the four models.…”
Section: Global Geopotential Modelmentioning
confidence: 99%
“…Table 1 presents data regarding the content of satellite data and the highest degree of order for the four models. Tongji-GGMG2021s 2022 300 S (Goce), S (Grace) [30] Tongji-Grace02k 2018 180 S (Grace) [30] a where A is for altimetry, S is for satellite (e.g., GRACE, GOCE, LAGEOS), G is for ground data (e.g. terrestrial.…”
Section: Global Geopotential Modelmentioning
confidence: 99%
“…Y. Wu et al (2021) estimated the standard deviation of XGM2019e_2159 using airborne gravity data in the Xisha Islands to be around 3.1 mGal. To begin, the free-air gravity disturbance was subtracted from low-degree spherical harmonics up to degree of 21 to eliminate the effect of mantle and deep Earth inhomogeneities (Bagherbandi & Sjöberg, 2012), as illustrated in Figure 9a.…”
Section: Gravity Strippingmentioning
confidence: 99%
“…A satellite-only GGM, namely, GOCO06S, was used to represent the longwavelength component of XGM2019e_2159, and the gravimetric data sources from National Geospatial-Intelligence Agency (NGA) and DTU13GRA were used to compute the shortwavelength component of this model [46]. The validation against local airborne gravimetric observations demonstrated that XGM2019e_2159 had improved precision, by a magnitude of ~1 mGal, compared to the GGMs that have similar expansion degrees [47].…”
Section: Local Refinement With Sar-based Altimetric Gravity Datamentioning
confidence: 99%